EDUCATION FINANCING MANAGEMENT: Study at Binamitra Cikarang Vocational High School - Madropi Madropi; Aprilliantoni Aprilliantoni (Almarhalah, 2022)
AbstractThis study aims to determine the Education Financing Planning, which is in SMK Binamitra Cikarang. The method used is descriptive qualitative research method. Respondents in this study were school principals, heads of administration, administrative staff, and several parents and guardians of students. The source of funds owned by Binamitra Vocational School comes from the foundation's own funds, funds from student guardians for education funding, funds from the central government (BOS) and funds from the district (BPMU), as well as temporary assistance from several companies. In the economic context, the total short-term cost is the same as the fixed cost plus the variable cost. By looking at the existing financing at Binamitra Vocational School, it is divided into three financing costs, namely investment costs, personal costs and operational costs. All of which are described in the RAPBS of Binamitra Vocational High School. From the results of the research, that for the running of the RAPBS at Binamitra Vocational School through the stages, namely: 1) planning, 2) implementation, and 3) reporting and evaluation. To avoid program errors, there must be an evaluation. Evaluation is usually done two weeks a month. From the results of data analysis, the research findings are as follows: the 100% agreed budget has not been fully realized, there are still changes to be improved.Keywords: Management, Education Financing, SMK Binamitra Cikarang